Evaluation of three viral concentration methods for detection and quantification of SARS-CoV-2 in wastewater. (10th February 2023) - Othman, Ines; Helmi, Amna; Slama, Ichrak; Hamdi, Rawand; Mastouri, Maha; Aouni, Mahjoub
Abstract: Wastewater-based epidemiology (WBE) could be useful as an early warning system for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic spread. Viruses are highly diluted in wastewater. Therefore, a virus concentration step is needed for SARS-CoV-2 wastewater detection. We tested the efficiency of three wastewater viral concentration methods: ultrafiltration (UF), electronegative membrane filtration and aluminum hydroxide adsorption–elution. We spiked wastewater with inactivated SARS-CoV-2 and we collected 20 other wastewater samples from five sites in Tunisia. Samples were concentrated by the three methods and SARS-CoV-2 was quantified by reverse transcription digital PCR (RT-dPCR). The most efficient method was UF with a mean SARS-CoV-2 recovery of 54.03 ± 8.25. Moreover, this method provided significantly greater mean concentration and virus detection ability (95%) than the two other methods. The second-most efficient method used electronegative membrane filtration with a mean SARS-CoV-2 recovery of 25.59 ± 5.04% and the least efficient method was aluminum hydroxide adsorption–elution. This study suggests that the UF method provides rapid and straightforward recovery of SARS-CoV-2 in wastewater. HIGHLIGHTS: Spiked wastewater with inactivated SARS-CoV-2 was used to compare the recovery of three viral concentration methods. Untreated municipal wastewater samples collected from five sites in Tunisia were used to compare the detection sensitivity of the three viral concentration methods. UF showed the best recovery and virus detection ability in wastewater samples. Graphical Abstract